CLOSE ADULT AS A MODEL OF SUBJECTIVITY FOR THE DEVELOPING PERSONALITY OF THE CHILD IN LIGHT OF THE IDEAS OF L. S. VYGOTSKY - Suvorova, Veniaminovna; Sorokopumova, Svetlana; Shutova, Natalia; Mamonova, Elena; Minaeva, Elena; Ivanova, Natalia (Revista Inclusiones, 2020)
This article presents the results of a comparative research study of the synergy between children and their parents. The goal of this research was to study the influence of parental agency on the personality development of preschool and junior school children. The research revealed that the role of a significant adult as an agency model for a child is a reciprocation mechanism. Analysis of the empirical data (N1=157 - senior preschoolers and their parents N3=157; N2=121 - junior school children and their parents N4=121) showed that the agency index of junior school children’s parents grew more in comparison to the agency index of preschool children’s parents. Further, the analysis identified two different types of parental agency. One type is defined as parents with “external activity” and the other as parents with “internal activity.” Within these groups, there are two different categories: parents of preschoolers and parents of junior school children. The qualities of external activity among parents of preschoolers include conscious activeness, freedom of choice, and responsibility for a child. These traits correspond to the play stage of child development. Parents of junior school children promote values including self-development and understanding and acceptance of others. These correspond with the goals of mastering social competence, particularly in school.